Penggunaan bahasa baku dalam penyajian informasi akuntansi di dunia usaha - Saddam Rizky Prambudi; Brinoel Felix Purba (JLT Jurnal Linguistik Terapan, 2025)
This study aims to investigate the importance of using standard language in the presentation of accounting information within the business sector in Indonesia. In the era of globalization and digitalization, accounting information that is clear, consistent, and compliant with established standards is essential for strategic decision-making. This research highlights the challenges faced by MSMEs in preparing financial statements that meet accounting standards, as well as the implications for access to financing and regulatory compliance. Through literature analysis and case studies, this study provides recommendations to improve the quality of financial reporting, strengthen transparency, and align national practices with international standards.